Comparison Between Viola-Jones and KLT Algorithms and Error Correction of Viola-Jones algorithm - Islam, Mohammad Ashraful; Naeem, Md. Anin; Hasan, Md. Nazmul (IJRDO -Journal of Computer Science Engineering, 2017)
Face detection is the first step of automated face recognition process in all pattern matching or artificial intelligence or robotic vision system. There are many face detection algorithms and they have their own strengths and limitations in terms of speed and accuracy in different situations. Viola-Jones and KLT are two well known algorithms used for real time face detection and they work differently. Viola-Jones algorithm is much faster even though it is proved to be erroneous in some specific circumstances. KLT is basically used for tracking by points feature in frames. In this paper, we have given an overview of these two algorithms and made comparative analysis amongst them. Later we have proposed a method that improves the accuracy of Viola-Jones algorithm by removing/minimizing false detection.